2001
DOI: 10.1210/er.22.3.289
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen and Spermatogenesis

Abstract: Although it has been known for many years that estrogen administration has deleterious effects on male fertility, data from transgenic mice deficient in estrogen receptors or aromatase point to an essential physiological role for estrogen in male fertility. This review summarizes the current knowledge on the localization of estrogen receptors and aromatase in the testis in an effort to understand the likely sites of estrogen action. The review also discusses the many studies that have used models employing the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
229
1
15

Year Published

2003
2003
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 454 publications
(254 citation statements)
references
References 0 publications
9
229
1
15
Order By: Relevance
“…Since the 1930s, estrogens have been known to be synthesized in male vertebrates (Zondek 1934), but with respect to male reproduction, this finding has been largely ignored for a long time because estrogens were considered to be exclusively female hormones with no role in spermatogenesis (reviewed by O'Donnell et al 2001). However, it has become quite clear now that E2 is an essential hormone in male reproduction (Hess et al 1997(Hess et al , 2001Sharpe 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Since the 1930s, estrogens have been known to be synthesized in male vertebrates (Zondek 1934), but with respect to male reproduction, this finding has been largely ignored for a long time because estrogens were considered to be exclusively female hormones with no role in spermatogenesis (reviewed by O'Donnell et al 2001). However, it has become quite clear now that E2 is an essential hormone in male reproduction (Hess et al 1997(Hess et al , 2001Sharpe 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Spermatogenesis is controlled by gonadotrophins and testosterone and is modulated by a complex network of endocrine and paracrine factors, among which are estrogens [1]. The biological effects of 17b-estradiol (E 2 ) are mediated by the estrogen receptors a (ERa) and b (ERb), which belong to the nuclear receptor superfamily and function as ligand-induced transcriptional factors.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, recent studies have shown that steroids, such as oestradiol-17b, testosterone and progesterone, can inhibit the transport activity of Bcrp and upregulate Bcrp expression and its cellular localisation in cancer cells, endothelial cells of the brain and endocrine organs. 21,41,42 Steroids, particularly testosterone and oestrogens, are known to regulate BTB and testicular Bcrp and spermatogenesis XJ Qian et al 456 function, [43][44][45][46] and Bcrp plays a significant role in regulating the transport of steroids across the myoid cells and Sertoli cells at the apical ES (Table 1). Additionally, the activity, expression and cellular distribution of Bcrp are regulated by steroids.…”
Section: Substratesmentioning
confidence: 99%